2023
DOI: 10.1007/s10943-023-01761-3
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Integration of Religion and Spirituality into the Mental Health Care of Culturally and Linguistically Diverse Populations in Australia: A Rapid Review

Abstract: Australia is a multicultural and linguistically diverse country. Despite the vital role of religion/spirituality in the mental health of people from culturally and linguistically diverse (CALD) backgrounds, it is not commonly included in their mental health care. A rapid review was conducted to critically evaluate the studies that identified relevant religious/spiritual aspects regarding mental health care for CALD communities. After a systematic search and screening, sixteen empirical studies were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…The study revealed that the intervention was effective to improve the major domains of mental health literacy at both the immediate post-intervention and 12 weeks follow up evaluation when compared with the baseline findings for each group. These findings are consistent with other studies among religious leaders across knowledge (Gouniai et al, 2022), perception (Han et al, 2023), attitude (Holleman & Chaves, 2023) and help-giving (Malviya, 2023;Slewa-Younan, et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The study revealed that the intervention was effective to improve the major domains of mental health literacy at both the immediate post-intervention and 12 weeks follow up evaluation when compared with the baseline findings for each group. These findings are consistent with other studies among religious leaders across knowledge (Gouniai et al, 2022), perception (Han et al, 2023), attitude (Holleman & Chaves, 2023) and help-giving (Malviya, 2023;Slewa-Younan, et al, 2020).…”
Section: Discussionsupporting
confidence: 92%